Study of Some Immunologic Parameters in Aborted Women Infected with Toxoplasma Gondii - Husham, Hiba Aeiad; Al-Mussawi , Kawther A. M. (Journal La Lifesci, 2024)
The demographic data of the patients was collected using a pre-designed questionnaire that included information on age and exposure to animals. Written permission was obtained from all participants in this research.The research was conducted in Karbala Maternity and Pediatric Hospital as well as other private labs in Kerbala city, Iraq, from November 2022 to May 2023. The blood samples underwent centrifugation, and the levels of serum IgM, IgG, interleukin-27 (IL-27), and Monocyte Chemoattractant Protein-1 (MCP-1) were measured using the enzyme-linked immunosorbent assay (ELISA) technique. The findings indicated that a total of 53 female individuals had abortion as a direct consequence of toxoplasmosis infection. The age group with the greatest incidence rate (56.6%) of toxoplasmosis was 18-26 years, whereas 79.2% of the patients were found to have had contact with animals. The blood immunoglobulin level analysis revealed that 98.1% of patients exhibited positive IgG findings, while 1.9% tested positive for IgM. In contrast, all healthy women in the control group tested negative for both IgM and IgG. The study found that women infected with toxoplasmosis had significantly higher levels of serum IL-27 (645.95 pg/ml) compared to the control group (88.26 pg/ml). Similarly, the infected women had significantly higher levels of MCP-1 (272.20 pg/ml) compared to the control group (48.83 pg/ml). These differences in interleukin levels were highly significant (P<0.0001). The present investigation indicates that women with recurrent abortion who were infected with T. gondii had elevated levels of IgG, IL-27, and MCP-1.